Comparison of Platelet Rich Plasma Concentrate and Corticosteroid in Treatment Oflateral Epicondylitis - MUHAMMAD KAMRAN KHAN, MUHAMMAD HANIF,, MUHAMMAD USMAN KHALID (Journal of Fatima Jinnah Medical University, 2018)
Lateral epicondylitis (LE), also known as Tennis Elbow is the commonest causes of musculoskeletal pain around the elbow which involves common extensor origin of the forearm. The disorder is a result of repetitive manual work which involves overexertion of extensors of wrist and finger and causes significant disability in terms of quality of daily life activities. Corticosteroid injection has been used as the treatment of choice for LE and platelet rich plasma (PRP) is an increasingly popular treatment for LE. Objectives: To compare the outcome of platelet rich plasma (PRP) and corticosteroid (CS) in treatment of Lateral Epicondylitis (LE). Study design: Randomized controlled trial Setting: Orthopaedic Department Mayo Hospital Lahore. Duration of study with dates: This study was conducted over a period of 12 months from 05-05-2014 to 04-05-2015. Subjects and methods: A total of 100 patients (50 in each group) were included in this study. Group-A and Group B received PRP and corticosteroid injection respectively through a peppering needling technique. Results: Mean age of the patients was 39.38±10.58 and 43.00±8.04 year in group-A and B, respectively. VAS pain score at baseline was in group-A 7.38±1.38 and 7.62±1.42 in group-B (p=0.395), at 2 weeks 6.70±1.05 in group-A and 6.28±1.37 in group-B (p=0.080), at 4 weeks 4.78±1.18 in group-A and 5.58±1.66 in group-B (p=0.007), at 6 weeks 3.88±1.02 in group-A and 4.54±1.48 in group-B (p=0.011) while pain score at 8 weeks was 2.60±1.08 in group-A and 3.28±1.65 in group-B (p=0.017). DASH score at baseline was 78.70±7.20 in group-A and 79.52±9.08 in -B (p=0.594), at 2 weeks 65.40±8.99 in group-A and 64.90±8.11 in group-B (p=0.771), at 4 weeks 53.20±8.58 in group-A and 54.00±7.82 in group-B (p=0.627), at 6 weeks 42.10±7.95 in group-A and 43.50±7.37 in group-B (p=0.364) while DASH score at 8 weeks was 28.80±6.41 in group-A and 34.50±7.96 in group-B (p<0.001). Repeated measure ANOVA was applied and presented in Table 6 and 7. ANOVA with stratification for age, gender and education also carried out. Conclusion: PRP group revealed significantly lower pain (VAS) at 4th, 6th and 8th and improved functional activities using DASH score at 8th week